Millenium journal of international studies
Millennium: Journal of International Studies aims to publish the most innovative peer-reviewed articles from the discipline of international studies, as well as original thinking from elsewhere in the social sciences with an international dimension. Interdisciplinary and wide-ranging in scope, the journal provides a forum for discussion on the latest developments in the theory of international relations, welcoming innovative and critical approaches.